Arquitetura e modernidades na educação secundarista em Goiânia (1937- 1971) - Cardoso, Bárbara Maria (2020)
Resumo em língua estrangeira: The present study seeks to investigate schoolar architecture in Goiânia from two ensembles of buildings, corresponding to different periods of Modernity: the first one, related to the stage of construction of the city, from 1933 to 1950, and the second one, in the stage of consolidation of the city – related to its growth, from 1950 to 1971 – a moment marked by the search for progress in the country and in the state of Goiás, when there was a change in paradigms in Brazilian education with the rupture of teaching patterns adopted until then. The purpose of the research, in the field of Theory and History of Architecture, is to observe how the transformations in the selected school buildings took place, in both scenarios, based on analytical categories and architectural and urbanistic attributes. Initially, it is necessary to recover the historical context and the approach of the theoretical paradigms of Education to understand the pedagogical assumptions and programmatic needs - and of Architecture - as a translation of the educational needs -, referring to the time frame. Thus, the two architectural ensembles will be confronted as to the characteristics - typological, compositional, plastic-formal, functional, constructive and tectonic - and urban - implementation, relationship in the urban landscape and in the history of the city. The contribution to the historiography of Goiânia applied to Education, in addition to the documentation itself, can stimulate reflections about Architecture, Education and the city.